Tangential Microfiltration of blackberry (Rubus adenotrichus Schltdl.) juice sweetened with stevia (Stevia rebaudiana Bertoni) - González-Torrivilla, César; Vaillant-Barka, Fabrice; Tapia-González, María Soledad (Revista de Ciencias Agrícolas, 2019)
The modern consumer values those components that can promote their well-being and help them reduce the risk of diseases the use of steviolglucosides as a sweetener in the formulation of foods is promising. The study evaluated the tangential microfiltration for clarification and conservation of blackberry juice sweetened with dried leaves of stevia. Two ceramic membranes were evaluated. The tests were performed at 35°C in concentration mode at a constant transmembrane pressure and tangential velocity. The formulation of the juice was defined through sensory evaluation tests. Volume, flow permeate, temperature, and pressure input and output were registered. The results of the variables analyzed in the process, as well as the physicochemical characterization of clarified juice, helped define the operating conditions for draw two formulations of microfiltrated juice, sweetened with stevia or sucrose, and thus evaluate the effectiveness of microfiltration as a conservation treatment. Aciduric microorganisms were quantified; molds and yeasts were carried out in the generated pasteurized samples stored at five different temperatures (5, 20, 30, 37, and 45°C). The recovery permeate juice obtained was 84.62%. The permeate Flow (Jp), exhibited higher values ​​at 40L/hm2. Also, the concentration of stevioside and rebaudioside A in the retentate increased with advancing ultrafiltration. A significant variation in color, turbidity, and soluble solids, was observed, unlike the pH. Also, its chemical and microbiological stability is confirmed that allows you to preserve quality during 27 days of storage.